Mini soft cheese as a simple model for biochemical studies on cheese-making and ripening - Milesi, Maria Mercedes (2007)
A new miniature cheese model obtained under controlled microbiological conditions was proposed, characterized and tested for reproducibility. Optimal heat treatment of cheesemilk was defined, as well as maximal ripening time. Miniature cheeses were obtained with batch pasteurized milk (65 °C, 30 min) and ripened at 5 °C. Lactic and nonlactic microbial populations were monitored by plate counts. Proteolysis was assessed by nitrogen fractions, electrophoresis and liquid chromatography, and a sniffing test was applied to evaluate aroma. Coliform bacteria decreased during ripening but moulds and yeasts increased up to 104 cfu/g after 60 d, which defined the end of ripening period. Starter population remained constant during all ripening (109 cfu/g), while nonstarter lactic acid bacteria increased from ~102 to 104 cfu/g. Soluble nitrogen levels at pH 4.6, in trichloracetic acid (0.73 mol/l) and in phosphotungtic acid (0.009 mol/l) were 151, 67, and 10 g/1000 g of the total nitrogen, respectively, after 60 d of ripening, which are usual values for soft cheeses. Proteolytic patterns as measured by electrophoresis were also similar to those of standard cheeses, as well as the aroma of the products. Peptide profiles revealed that the areas of most peaks increased with ripening time. The proposed model showed to be suitable for the production of mini cheese specimens for laboratory testing of cultures and enzymes in similar conditions to their real environment in the food matrix.